Impact of macrophages on tumor growth characteristics in a murine ocular tumor model. (October 2016) - Stei, Marta M.; Loeffler, Karin U.; Kurts, Christian; Hoeller, Tobias; Pfarrer, Christiane; Holz, Frank G.; Herwig-Carl, Martina C.
Abstract: Tumor associated macrophages (TAM), mean vascular density (MVD), PAS positive extravascular matrix patterns, and advanced patients' age are associated with a poor prognosis in uveal melanoma. These correlations may be influenced by M2 macrophages and their cytokine expression pattern. Thus, the effect of TAM and their characteristic cytokines on histologic tumor growth characteristics were studied under the influence of age. Ninety five CX3 CR1 +/GFP mice (young 8–12weeks, old 10–12months) received an intravitreal injection of 1 × 10 5 HCmel12 melanoma cells. Subgroups were either systemically macrophage-depleted by Clodronate liposomes (n = 23) or received melanoma cells, which were pre-incubated with the supernatant of M1- or M2-polarized macrophages (n = 26). Eyes were processed histologically/immunohistochemically (n = 75), or for flow cytometry (n = 20) to analyze tumor size, mean vascular density (MVD), extravascular matrix patterns, extracellular matrix (ECM) and the presence/polarization of TAM. Prognostically significant extravascular matrix patterns (parallels with cross-linkings, loops, networks) were found more frequently in tumors of untreated old compared to tumors of untreated young mice (p = 0.024); as well as in tumors of untreated mice compared to tumors of macrophage-depleted mice (p = 0.014). Independent from age, M2-conditioned tumors showed more TAM (p = 0.001), increased collagen IV levels (p = 0.024) and a higher MVD (p = 0.02) than M1-conditioned tumors. Flow cytometry revealed a larger proportion of M2-macrophages in old than in young mice. The results indicate that TAM and their cytokines appear to be responsible for a more aggressive tumor phenotype. Tumor favoring and pro-angiogenic effects can be directly attributed to a M2-dominated tumor microenvironment rather than to age-dependent factors alone. However, an aged immunoprofile with an increased number of M2-macrophages may provide a tumor-favoring basis. Further, old mice represent a more suitable tumor model instead of young mice since their histologic tumor pattern better resembles human tumors. Highlights: An aged immunoprofile provides a M2 macrophage-dominated basis for tumor malignancy. M2 macrophages directly influence the mean vascular density and stroma remodelling. Tumor progression is functionally correlated to M2 macrophages in vivo and in vitro . Old mice represent a better animal tumor model and should be used in studies.